2011
DOI: 10.1590/s0103-166x2011000200006
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade de vida e transplante de células-tronco hematopoéticas alogênico: um estudo longitudinal

Abstract: Este estudo teve como objetivo avaliar a qualidade de vida de pacientes submetidos ao transplante de células-tronco hematopoéticas alogênico, comparando as fases pré-transplante de células-tronco hematopoéticas, o momento do isolamento protetor na Enfermaria e o pós-transplante de células-tronco hematopoéticas imediato. A amostra foi composta por sete pacientes (quatro homens e três mulheres) submetidos ao transplante de células-tronco hematopoéticas no primeiro semestre de 2008. Na coleta de dados foi utiliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0
16

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 20 publications
2
4
0
16
Order By: Relevance
“…However, a review performed in Germany with the main QOL studies using the QLQ-C30 to evaluate the pre-and post-HSCT (11) , and another review performed in Chicago (USA) that compared the QOL of patients undergoing autologous and allogeneic HSCT in 105 participants with cancer, showed the patients' age was between 40 and 50 years (12) , which differs from the present study findings. The marital status and number of children in this study corroborate data found in national and international literature, i.e., patients with hematological malignancies are married or in a common-law marriage and have one to three children (12)(13)(14)(15)(16) . In a study on the bond between cancer patients and their families, it was observed that the main companions of patients with neoplasia are children, spouses and parents, and family involvement is critical during the disease process.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…However, a review performed in Germany with the main QOL studies using the QLQ-C30 to evaluate the pre-and post-HSCT (11) , and another review performed in Chicago (USA) that compared the QOL of patients undergoing autologous and allogeneic HSCT in 105 participants with cancer, showed the patients' age was between 40 and 50 years (12) , which differs from the present study findings. The marital status and number of children in this study corroborate data found in national and international literature, i.e., patients with hematological malignancies are married or in a common-law marriage and have one to three children (12)(13)(14)(15)(16) . In a study on the bond between cancer patients and their families, it was observed that the main companions of patients with neoplasia are children, spouses and parents, and family involvement is critical during the disease process.…”
Section: Discussionsupporting
confidence: 87%
“…A similar economic pattern was found in national and international studies (10,(12)(13)18) . Among the many negative events of neoplasia, the financial difficulty is responsible for vulnerable conditions.…”
Section: Discussionsupporting
confidence: 84%
“…Trata-se de um procedimento altamente invasivo e que envolve risco de morte em decorrência de seus efeitos adversos (Matias, Oliveira-Cardoso, Mastropietro, Voltarelli, & Santos, 2011). Por isso, exige o envolvimento intenso de um cuidador familiar durante todas as suas etapas, o que expõe esse membro da família a estressores contínuos (Laudenslager et al, 2015;Rodday et al, 2012).…”
Section: Introductionunclassified
“…[8][9] The conditioning phase can be highlighted among the decisive steps throughout the HSCT process, in which the patient receives chemotherapy and/or radiotherapy to cause medullary aplasia and induce immunosuppression with the purpose of avoiding rejection of the new grafted bone marrow. [10][11] At this stage, the patient suffers from symptomatologies arising from the administered drugs, and gastrointestinal disorders are common.…”
Section: Introductionmentioning
confidence: 99%